Treadmill training does not enhance skeletal muscle recovery following disuse atrophy in older male mice - Yee, Elena M.; Hauser, Carson T.; Petrocelli, Jonathan J.; de Hart, Naomi M. M. P.; Ferrara, Patrick J.; Bombyck, Princess; Fennel, Zachary J.; van Onselen, Lisha; Mookerjee, Sohom; Funai, Katsuhiko; Symons, J. David; Drummond, Micah J. (Frontiers in Physiology, 2023)
A hallmark of aging is poor muscle recovery following disuse atrophy. Efficacious strategies to enhance muscle recovery following disuse in aging are non-existent. Prior exercise training could result in favorable muscle morphological and cellular adaptations that may promote muscle recovery in aging. Here we characterized the impact of exercise training on skeletal muscle inflammatory and metabolic profiles, cellular remodeling and function, together with femoral artery reactivity prior to and following recovery from disuse atrophy in aged male mice. We hypothesized that 12-weeks of treadmill training in aged male mice would improve skeletal muscle cellular remodeling at baseline and during recovery from disuse resulting in improved muscle regrowth. Physical performance, ex vivo muscle and vascular function, tissue and organ mass, hindlimb muscle cellular remodeling (macrophage, satellite cell, capillary, myofiber size, fibrosis) and proteolytic, inflammatory and metabolic muscle transcripts were evaluated in aged exercise trained and untrained mice. We found that at baseline following exercise training (vs sedentary mice), exercise-capacity and physical function increased, fat mass decreased, and endothelial function improved. However, exercise training did not alter tibialis anterior or gastrocnemius muscle transcriptional profile, macrophage, satellite cell, capillarity or collagen content, or myofiber size and only tended to increase tibialis mass during recovery from disuse atrophy. While exercise training in old male mice improved endothelial function, physical performance, and whole-body tissue composition as anticipated, 12-weeks of treadmill training had limited impact on skeletal muscle remodeling at baseline or in response to recovery following disuse atrophy.